Readiness for transfer: a mixed-methods study on ICU transfers of care - Amartya Mukhopadhyay; Chee-Kiat Tan; Soo-Hoon Lee; Phillip Phan; Clarice Wee; Yanika Kowitlawakul (BMJ Open, 2023)
Objective Past studies on intensive care unit (ICU) patient transfers compare the efficacy of using standardised checklists against unstructured communications. Less studied are the experiences of clinicians in enacting bidirectional (send/receive) transfers. This study reports on the differences in protocols and data elements between receiving and sending transfers in the ICU, and the elements constituting readiness for transfer.Methods Mixed-methods study of a 574-bed general hospital in Singapore with a 74-bed ICU for surgical and medical patients. Six focus group discussions (FGDs) with 34 clinicians comprising 15 residents and 19 nurses, followed by a structured questionnaire survey of 140 clinicians comprising 21 doctors and 119 nurses. FGD transcripts were analysed according to the standard qualitative research guidelines. Survey data were analysed using Student’s t-test with Bonferroni corrections.Results General ward (GW) clinicians are more likely to receive ICU patients with complete discharge summaries while ICU clinicians receiving GW patients get significantly less data. Emergency department (ED), GW and operating theatre physicians accompany their patients to the ICU while ICU nurses accompany their patients to the GW. Not all units, such as the ED, experience bidirectional transfers.Conclusion The protocols and supporting data elements of an ICU transfer vary by the type of transfer and transferring unit. Readiness for transfer means that sending unit protocols affirmatively consider the needs of the receiving unit’s data needs and resource constraints.